METAPHORS OF ORCHID NAMES IN INDONESIAN - I Dewa Putu Wijana (UIBU, 2023)
This article aims to reveal several matters concerning metaphorical expressions found in orchid naming practices in Indonesian. By using data collected through google tracing, it is found that many orchid names in Indonesian consist of metaphorical expressions located on the